2014
DOI: 10.1186/1755-7682-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic inflammation on level of ferritin seminal in chronic renal male patient undergoing hemodialysis

Abstract: BackgroundMost hemodialysis patients present with chronic systemic inflammation characterized by the elevation of serum C-reactive protein (CRP) levels and/or the production of proinflammatory interleukins by the immune system in response to the hemodialysis process. Plasma ferritin(PF) is one of the parameters used to correct anemia. An PF level of >500 ng/mL is not recommended for correction of anemia because of the uncertainty of whether these levels are elevated because of anemia or a mere reaction to infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…10 Our results suggest that only ST levels were signifi cantly lower in the seminal plasma of uremic patients (p <0.001). This result is corroborated by other previous studies conducted by different researchers in non-uremic populations with suspected sub/infertility as Koşar et al 11 (16,58.1±14.4 μg/ ml vs 108.4±17.5 μg/ml); Bharshankar and Bharshankar 12 (2.63±1.76 mg/dl vs 5.35±2.07 mg/dl, 91±51 μg/ml), and Saeed et al 13 [17, 54. The explanation for a decrease in mean ST levels in unhealthy men and its correlation with SQ observed in this and other sub/infertility studies are not well known. However, it is speculated that it is multifactorial and by various mechanisms, with participation of immunological, hormonal, ure-mic, oxidative, and infl ammatory factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…10 Our results suggest that only ST levels were signifi cantly lower in the seminal plasma of uremic patients (p <0.001). This result is corroborated by other previous studies conducted by different researchers in non-uremic populations with suspected sub/infertility as Koşar et al 11 (16,58.1±14.4 μg/ ml vs 108.4±17.5 μg/ml); Bharshankar and Bharshankar 12 (2.63±1.76 mg/dl vs 5.35±2.07 mg/dl, 91±51 μg/ml), and Saeed et al 13 [17, 54. The explanation for a decrease in mean ST levels in unhealthy men and its correlation with SQ observed in this and other sub/infertility studies are not well known. However, it is speculated that it is multifactorial and by various mechanisms, with participation of immunological, hormonal, ure-mic, oxidative, and infl ammatory factors.…”
Section: Discussionsupporting
confidence: 86%
“…Little is known about SF behavior in seminal plasma. Silva et al 16 did not fi nd a change in the SF seminal level in uremic and non-uremic patients in a sample of 60 hemodialysis patients. On the other hand, Wan et al 17 found higher concentrations of SF in seminal plasma of 62 men with infertility infected by Chlamydia trachomatis.…”
Section: Discussionmentioning
confidence: 86%
“…Ferritin is an intracellular protein that stores iron in the atoxic form, and it is found in the extracellular environment as a result of cellular synthesis and secretion. Seminal ferritin is found in abundance in the seminal plasma, and Sertoli cells produce approximately 70% of its contents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…al [28] studying effect of systemic inflammation on level of ferritin seminal in chronic renal male patient undergoing hemodialysis, using similar methodology, examined a sample of 60 patients on HD and did not find differences or correlations of SF levels among patients with inflammation, without inflammation, and controls (p > 0.05). Wan et al [29] investigated the association between chlamydia trachomatis infection and the contents of seminal plasma ferritin, β-2-microglobulin, and total protein in seminal plasma of 30 fertile men (normal group) and 62 men with infertility infected by chlamydia trachomatis.…”
Section: Fertility Index (Fi) and Seminal Parameters (Sp)mentioning
confidence: 99%
“…Silva et. al [28] evaluated patients with chronic systemic inflammation with consolidated adaptive process; Wan et al [29]evaluated patients with acute local or subacute infection. With resolution of an acute infectious stimulus, proinflammatory cytokines and SF levels tend to normalize [30].…”
Section: Fertility Index (Fi) and Seminal Parameters (Sp)mentioning
confidence: 99%